Fundamentals and analytical applications of multiway calibration - Munoz de la Pena, Arsenio; Olivieri, Alejan C.; Escandar, Graciela M.; Goicoechea, Hector C. (Data handling in science and technology, 2015)
Fundamentals and Analytical Applications of Multi-Way Calibration presents researchers with a set of effective tools they can use to obtain the maximum information from instrumental data. It includes the most advanced techniques, methods, and algorithms related to multi-way calibration and the ways they can be applied to solve actual analytical problems. This book provides a comprehensive coverage of the main aspects of multi-way analysis, including fundamentals and selected applications of chemometrics that can resolve complex analytical chemistry problems through the use of multi-way calibration.